Effects of static stretching in warm-up on repeated sprint performance - Sim, A. Y.; Dawson, B. T.; Guelfi, K. J.; Wallman, K. E.; Young, W. B. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to examine the effects of static stretching during warm-up on repeated sprint performance and also to assess any influence of the order in which dynamic activities (i.e., run-throughs and drills) and static stretching are conducted. Thirteen male team sport players completed a repeated sprint ability test consisting of three sets of maximal 6 × 20-m sprints (going every 25 seconds) after performing one of three different warm-up protocols in a within-subjects counterbalanced design. Each warm-up protocol involved an initial 1000-m jog, followed by either dynamic activities only (D), static stretching followed by dynamic activities (S-D), or dynamic activities followed by static stretching (D-S). First (FST), best (BST) and total (TST) 20-m sprint times were determined for each individual set of the repeated sprint ability test and overall (3 sets combined). Although consistent significant differences were not observed between trials for TST, BST, and FST, the mean values for TST in all individual sets and overall were generally slowest in the D-S condition (D = 60.264 ± 1.127 seconds; S-D = 60.347 ± 1.774 seconds; D-S = 60.830 ± 1.786 seconds). This trend was supported by moderate to large effect sizes and qualitative indications of possible or likely benefits for TST, BST, and FST for the D and S-D warm-ups compared to D-S. No significant differences or large effect sizes were noted between D and S-D, indicating similar repeated sprint ability performance. Overall, these results suggest that 20-m repeated sprint ability may be compromised when static stretching is conducted after dynamic activities and immediately prior to performance (D-S).